Enhancing Mobile DeFi Transactions Through Blockchain‎Adoption: A Pythagorean Fuzzy AHP Study - Jain , Yogesh Kumar; Tak , Tan Kuan; Upreti , Kamal; Kumar , Nishant; Kshirsagar, Pravin R. (International Journal of Basic and Applied Sciences, 2025)
Blockchain technology has emerged as a pivotal enabler for innovation in mobile decentralized finance (DeFi) ecosystems. This study em-‎employs the Pythagorean Fuzzy Analytic Hierarchy Process (PF-AHP) to identify and rank critical enablers driving blockchain adoption for ‎enhancing mobile DeFi transactions. A structured three-stage methodology evaluates twenty-four sub-criteria across operational, managerial, ‎and strategic dimensions. Results emphasize managerially focused factors—such as reduced foreign exchange (FX) transfer costs and open-source adaptability—as the most critical enablers, followed by operational drivers like transparency. Sensitivity analysis confirmed the ro-‎robustness of these findings. The results offer actionable insights for fintech practitioners, digital strategists, and policymakers seeking to ‎optimize blockchain-based mobile financial platforms. By contributing to improved financial inclusion, operational efficiency, and regulatory ‎alignment, the study supports broader welfare enhancement in the digital economy. The proposed PF-AHP framework provides an empirical decision-making tool to guide innovation and strategic planning in financial technology services.